Numerical Simulation of Flow Field in Coaxial Tank Gun Recoil Damper (Advances in Military Technology, 2019)
To know the hydraulic resistance of tank gun hydraulic damper is essential to determine the barrel recoil parameters. Usage of one-dimensional analytical models simplifies the determination of the hydraulic resistance; however these models do not provide data about the flow nature inside the hydraulic damper. This paper studies the internal flow inside the hydraulic damper of the gun recoil system. The dynamic mesh technique using two-dimensional flow computational solver has been used. A User Defined Function (UDF) has been developed to feed the solver by the measured recoil velocity. The study shows that the liquid flow inside the hydraulic damper is complicated at the start of the gun recoil and it is quickly changing to a simpler flow pattern until the end of the recoil. Also, the liquid pressure inside the hydraulic damper has been measured and compared to the computational values.
Keywords: coaxial recoil system; dynamic mesh; hydraulic damper; recoil simulation